Validation of the Brazilian version of the hepatitis B quality of life evaluation instrument - HBQOL, and its application to patients with chronic hepatitis B in Cascavel - PR - Jessica Cristina Balbinot; Astrid Wiens Souza; Roberto Pontarolo; Orli Dutra Boeira Junior; Edson Antonio Alves da Silva; Daniele Schaab Boff Junges; Camila Borges dos Reis; Rafael Venson; Ana Flavia Redolfi Oliota; Andreia Cristina Conegero Sanches (Universidade de São Paulo, 2022)
Abstract The objective of this study is to validate the specific questionnaire for Hepatitis B HBQOL (Hepatitis B Quality of Life Instrument, version 1.0) for the Brazilian version, in addition to testing its applicability in patients with hepatitis B under treatment and comparing the quality of life between patients using first-line drugs (tenofovir and entecavir). For the validation, the back-translation technique was used in a sample of 47 patients. Factor analysis was performed between the items in each domain of the questionnaire and the internal consistency was calculated using Cronbach's α coefficient. In assessing the applicability of the validated questionnaire, interviews were carried out with 124 patients. Sociodemographic and treatment data were collected to characterize the sample and perform correlation analyzes. The results demonstrate that the Brazilian version of the questionnaire was successfully validated. In the analysis carried out among the 124 patients, the domains psychological well-being and stigma obtained the highest scores in quality of life and the lowest level of education conferred better results in these two domains. The comparison between tenofovir and entecavir showed no significant difference in patients' quality of life. The use of this validated instrument can make therapeutic decisions more rational.